Microbial toxicity of methyl tert-butyl ether (MTBE) determined with fluorescent and luminescent bioassays. (February 2015) - Roslev, Peter; Lentz, Trine; Hesselsoe, Martin
Highlights: We examined the microbial toxicity of methyl tert -butyl ether (MTBE). We targeted luminescent bacteria and yeast, and native groundwater microorganisms. A. fischeri was more sensitive to MTBE exposure than lux -tagged bacteria and yeast. Microbial alkaline phosphatase in groundwater was sensitive to MTBE exposure. Selected light based endpoints are suitable proxies for measuring MTBE toxicity. Abstract: The inhibitory effects of the fuel additive methyl tert -butyl ether (MTBE) and potential degradation products tert- butanol (TBA) and formaldehyde was examined using mixed microbial biomass, and six strains of bioluminescent bacteria and yeast. The purpose was to assess microbial toxicity with quantitative bioluminescent and fluorescent endpoints, and to identify sensitive proxies suitable for monitoring MTBE contamination. Bioluminescent Aliivibrio fischeri DSM 7151 (formerly Vibrio fischeri ) appeared highly sensitive to MTBE exposure, and was a superior test organisms compared to lu x-tagged Escherichia coli DH5α, Pseudomonas fluorescens DF57-40E7 and Saccharomyces cerevisiae BLYR . EC10 and EC50 for acute MTBE toxicity in A. fischeri were 1.1 and 10.9 mg L −1, respectively. Long term (24 h) MTBE exposure resulted in EC10 values of 0.01 mg L −1 . TBA was significantly less toxic with EC10 and EC50 for acute and chronic toxicity >1000 mg L −1 . Inhibition of bioluminescence was generally a more sensitive endpoint for MTBE toxicity than measuring intracellular ATP levels and heterotrophic CO2 assimilation. A weak estrogenic response was detected for MTBE at concentrations ⩾3.7 g L −1 using an estrogen inducible bioluminescent yeast strain ( S. cerevisiae BLYES). Microbial hydrolytic enzyme activity in groundwater was affected by MTBE with EC10 values of 0.5–787 mg L −1, and EC50 values of 59-3073 for alkaline phosphatase, arylsulfatase, beta-1, 4-glucanase, N-acetyl-beta-d -glucosaminidase, and leucine-aminopeptidase. Microbial alkaline phosphatase and beta-1, 4-glucanase activity were most sensitive to MTBE exposure with EC50 ⩽ 64.8 mg L −1 . The study suggests that bioassays with luminescent A. fischeri, and fluorescent assays targeting hydrolytic enzyme activity are good candidates for monitoring microbial MTBE toxicity in contaminated water.